PSYCHO-EDUCATIONAL CONTEXT OF SUPPORTING SENIORS IN POLAND , USING TOOLS FROM THE EDUSENIOR PROJECT - Kozerska, Agnieszka; Napora, Elżbieta; Piasecka, Małgorzata; Górna, Joanna; Gil, Alina; Nowacka, Urszula; Ochoa, Luis S. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The purpose of the article was to capture the psycho-educational context of support for Polish seniors by institutions that have used the methods developed in the Edusenior project. The areas requiring seniors’ education and the scope of work carried out by the developing institutions, government, and NGOs initiatives to raise the quality of life for seniors have been elucidated in the following article. The products obtained from the international Edusenior project, in which the preliminary results were evaluated by experienced Polish reviewers, comply with the above requirements.